MODERN RESEARCH AND PERSPECTIVES FOR PRODUCING ALTERNATIVE FUEL FROM BEET PULP - S. O. Semenikhin; V. O. Gorodetsky; N. M. Daisheva; N. I. Kotlyarevskaya (Новые технологии)
Beet pulp is a secondary resource of the sugar industry which consists mainly of high molecular weight polysaccharides. However, 1/8 of beet pulp is not demanded by domestic industry but this fact makes it promising as the main carrier of nutrients for the microbiological industry, in particular, the microbiological synthesis of alternative fuels. The article provides an overview of domestic and foreign scientific research on obtaining alternative fuel resources. The main ones are hydrogen, methane, ethanol, butanol and acetone. Currently, the highest yield of fuel resources obtained by the microbiological method reaches 0.4 g/g of sugars. When usingEscherichia coli, the end product is ethanol, and Clostridium beijerinckii is acetone and butanol.Methane production is at the level of 502.5 l/kg of volatile solids, and that of hydrogen is 197.9 ml/g of total carbon, however, the microorganisms used are not named by the authors. To achieve such indicators the method of preparing beet pulp is important, since it is necessary to hydrolyze the largest amount of polysaccharides into monosaccharides. So, pre-treatment of beet pulp with sulfuric acid can increase the degree of hydrolysis from 33% to 93%. In addition, beet pulp can be used to immobilize Saccharomyces cerevisiae when processing molasses or syrup solutions for ethanol synthesis, providing up to 7 fermentation cycles before the retention agent loses its properties. The production of ethanol in this case will be 0.446 g/g of sugars. The works aimed at a feasibility study of the feasibility of installing biogas plants at sugar factories for various regions of Russia are considered. However, since Russia is a country with significant reserves of fossil fuels, the payback period for the introduction of biogas plants is quite high.